Effects of the payout system of income taxes to municipalities in Germany. (April 2017) - Ultsch, Alfred; Behnisch, Martin
Abstract: The German system of allocating income tax revenues to municipalities is rather complex. Several layers of administration and legislation are involved, thereby hindering easy comprehension of the system. In general, national legislation demands that the funding a municipality receives from the state ( Land ) as a share of income tax revenues (output of the system) should be a fixed proportion of the total income tax yield of each municipality (input to the system). This work presents a nationwide examination of the input/output properties for all municipalities in Germany. Surprisingly, the system operates in two modes: municipalities receive either a large share (high quota) or a small share (low quota) of the input. A nationwide analysis of all municipalities revealed that, in general, municipalities located in eastern Germany receive a low quota of 10% and less. On the other hand, municipalities in western Germany (except some rural municipalities) are usually allocated a relatively high quota of 15% and more of the income taxes per taxpayer paid to the state. Highlights: The German system of allocating income tax revenues to municipalities is rather complex. The relationships between the Income Tax Yield and the Income Tax Share in Germany have not yet been analyzed at this scale. The payout system of income taxes to municipalities operates in two distinct modes: low quota and high quota. States enjoying comparatively high tax revenues allocate a larger proportion of money per taxpayer to their municipalities. The attempt to increase fiscal income by attracting new tax-paying residents increases the total pressure on land resources.